Regulation of Neuronal Excitability through Pumilio-Dependent Control of a Sodium Channel Gene - Mee, Christopher J. (J Neurosci, 2004)
Dynamic changes in synaptic connectivity and strength, which occur during both embryonic development and learning, have the tendency to destabilize neural circuits. To overcome this, neurons have developed a diversity of homeostatic mechanisms to maintain firing within physiologically defined limits. In this study, we show that activity-dependent control of mRNA for a specific voltage-gated Na(+) channel [encoded by paralytic (para)] contributes to the regulation of membrane excitability in Drosophila motoneurons. Quantification of para mRNA, by real-time reverse-transcription PCR, shows that levels are significantly decreased in CNSs in which synaptic excitation is elevated, whereas, conversely, they are significantly increased when synaptic vesicle release is blocked. Quantification of mRNA encoding the translational repressor pumilio (pum) reveals a reciprocal regulation to that seen for para. Pumilio is sufficient to influence para mRNA. Thus, para mRNA is significantly elevated in a loss-of-function allele of pum (pum(bemused)), whereas expression of a full-length pum transgene is sufficient to reduce para mRNA. In the absence of pum, increased synaptic excitation fails to reduce para mRNA, showing that Pum is also necessary for activity-dependent regulation of para mRNA. Analysis of voltage-gated Na(+) current (I(Na)) mediated by para in two identified motoneurons (termed aCC and RP2) reveals that removal of pum is sufficient to increase one of two separable I(Na) components (persistent I(Na)), whereas overexpression of a pum transgene is sufficient to suppress both components (transient and persistent). We show, through use of anemone toxin (ATX II), that alteration in persistent I(Na) is sufficient to regulate membrane excitability in these two motoneurons.